WEB-BASED SCREEN PRINTING PRODUCT DESIGN ORDERING SERVICES - Harvei Desmon Hutahaean; Wahyu Simangunsong; Veronica Elisabeth Simatupang; Rebecca Lyana Elisabeth; Rianni Yuni Sinaga; Sintia Natalia Br Sinulingga (Jurnal Mantik, 2021)
Website-based design and screen printing services business as a booking medium is a very promising business, this is due to the rapid development of the fashion world, especially those that are sweeping young people in the modern era now causing the need for increased availability of fashion. This can be seen with the rise of shopping centers that sell and advertise various fashion styles. Also do not miss the shops along the way that display displays of varied fashion styles. The new technology in the world of screen printing in the form of digital printing makes it easier and beautify the results of screen printing. Digital printing screen printing results look smoother and neater than conventional screen printing results. This business is classified as a business that can only be handled by professional people so it is rarely a mock-up of an art business like this. This makes business competitors still very few while the business opportunity is very large. Seeing the opportunity and seeing the potential that has made researchers initiate and pursue this business further.